Penerapan Restorative Justice Antara Korban Dan Pelaku Dalam Tindak Pidana Pencurian - Anton, Rudi (Universitas Jabal Ghafur, 2025)
Restorative justice is a process in which there is a way to resolve a crime and its impact in the future. The restorative justice approach in criminal acts of theft is a means of carrying out justice that is fully carried out and achieved by victims and perpetrators. The problem discussed in this research is the urgency of implementing restorative justice in the crime of theft? What is the concept of restorative justice as a form of criminal responsibility for the crime of theft that provides justice to victims and perpetrators? Normative juridical research methods. In conclusion, the urgency of implementing restorative justice in criminal acts of theft aims to realize the restoration of the condition of crime victims, perpetrators and interested communities (stakeholders) through a case resolution process that does not only focus on prosecuting and punishing the perpetrator, but focuses on recovery methods that involve the perpetrator of the crime, victims and their communities in the criminalization process by giving perpetrators the opportunity to realize their mistakes and repent, so that the perpetrators can return to the life of their community. The concept of Restorative Justice with the existence of a peace letter cannot eliminate criminal responsibility for the perpetrator. However, the existence of this peace is a relief for the perpetrator and is a concept of restorative justice, where negotiations have been carried out between the perpetrator and the victim. This peace is in line with the concept of restorative justice, namely a fair resolution. by emphasizing restoration to the original state and not retaliation.Keywords : Crime, Theft, Restorative Justice